Zinc Finger-Homeodomain and Mini Zinc Finger proteins are key players in plant growth and responses to environmental stresses. (10th May 2022) - Bollier, Norbert; Gonzalez, Nathalie; Chevalier, Christian; Hernould, Michel
Abstract: The ZINC FINGER-HOMEODOMAIN (ZHD) protein family is a plant-specific family of transcription factors containing two conserved motifs: a non-canonical C5H3 zinc finger domain (ZF) and a DNA-binding homeodomain (HD). The MINI ZINC FINGER (MIF) proteins belong to this family, but were possibly derived from the ZHDs by losing the HD. Information regarding the function of ZHD and MIF proteins is scarce. However, different studies have shown that ZHD/MIF proteins play important roles not only in plant growth and development, but also in response to environmental stresses, including drought and pathogen attack. Here we review recent advances relative to ZHD/MIF functions in multiple species, to provide new insights into the diverse roles of these transcription factors in plants. Their mechanism of action in relation to their ability to interact with other proteins and DNA is also discussed. We then propose directions for future studies to understand better their important roles and pinpoint strategies for potential applications in crop improvement. Abstract : This review describes recent advances dealing with the study of Zinc Finger-Homeodomain and Mini Zinc Finger protein functions during plant development and in response to environmental stresses.